Les parties du corps humain dans les phrasèmes à valeur intensive en français et en polonais – vers une étude contrastive - Izert, Małgorzata; Pilecka, Ewa (Studia Romanica Posnaniensia, 2023)
The first objective of this study is a contrastive analysis that will allow us to highlight the similarities (cf. jouer comme un pied/grać jak noga) and also the divergences (cf. faire des pieds et des mains pour qqch/bronić czegoś rękami i nogami) between phraseosomatisms [expressions with body-parts nouns] of intensifying value in French and Polish languages; as the examined phraseosomatisms are not always transparent, the usefulness of such studies for translating and for French language teaching is obvious. The second objective, which is closely related to the first, is to propose a detailed description of some selected expressions, to verify which parameters of such description should be integrated into the microstructure of our future bilingual Polish-French dictionary: Electronic Dictionary of Intensifying Expressions (in Polish: Słownik Elektroniczny Wyrażeń Intensyfikujących, or SEWI).